Implementasi Strategi Pemasaran Digital Melalui Media Sosial untuk Meningkatkan Penjualan UMKM : Studi Kasus: UD. Akbar Lestari - Al Fadila, Nadila; Jamil, Muhammad; Aris, Valentino (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study implements a digital marketing strategy via Instagram to increase sales at UD Akbar Lestari, a rattan craft MSME in Pangkep, Indonesia. Conventional, word-of-mouth marketing had constrained market reach, whereas social media enables visual storytelling and two-way interactions that strengthen brand awareness. We adopted a Research and Development (R&D) approach using the RACE framework—Reach, Act, Convert, Engage. Data were collected through interviews, observation, sales records, and Instagram Insights. The intervention comprised launching the official account @ud.akbarlestari, designing an informative profile, defining content pillars, scheduling posts, and deploying Feed, Reels, and Story formats with clear calls-to-action and a purchasing link in the bio. The study’s novelty lies in adapting RACE to a rural handicraft context and leveraging the local Pangkep dialect in Reels to deepen audience affinity. After one month, marketing performance improved markedly: the account reached 2,484 users and generated 4,771 impressions; there were 523 interactions from 122 accounts; 372 profile activities (330 visits; 42 external link clicks); and Linktree recorded 56 views with 27 clicks (48.21% CTR). Reels was the most effective format, achieving 1,840 views, reach of 1,211, 64 likes, 6 comments, and 37 shares. Business outcomes also strengthened, with sales increasing from IDR 11,341,500 to IDR 21,050,900 and evidence of repeat purchases, indicating emerging loyalty. In conclusion, RACE-based Instagram implementation effectively improves reach, engagement, conversion, and sales for craft MSMEs. We recommend maintaining content consistency, further optimizing Instagram features, and conducting regular Insight-driven evaluations to sustain performance gains.